Can Poverty Be Eradicated? An Islamic Perspective - Hanifah, Hani Siti; Tenaesah, Erna; Fadilah, Resmi Afifah; Merliyana, Reny Dany; Esen, Adem (Perhimpunan Intelektual Muslim Indonesia, 2024)
The research aims to describe poverty and strategic solutions in an Islamic perspective in Indonesia. The data sources from several literatures including the Qur'an, al-Hadith, books, and journals. The research uses a qualitative method and triangulation analysis technique as a strategy in data validity from data sources and themes coherently. The results of this study recommend that Islamic sharia is one of solution for poverty, both natural, cultural and structural poverty. The mechanism of Islamic sharia in overcoming poverty is to ensure the fulfillment of primary needs, ownership regulation, employment availability and provision of access to education. The mechanism will function properly on the condition that the state must be fully responsible with the support of the sharia system such as the judiciary, honest apparatus and governance of the state treasury (baitul mal) based on Islam. This research is expected to add insight into Islamic economics and futher research.